Pengaruh Bauran Pemasaran terhadap Keputusan Pasien dalam Memilih Layanan Kesehatan Rumah Sakit: Literature Review - Fahnida Zeydra Thohari; Ede Surya Darmawan (Syntax Corporation, 2023)
The quality of health care must start from the patient's needs and end with the patient's perception, where the patient's perception of the quality of service is an overall assessment of the excellence of a health care. Patients as consumers will selectively choose hospitals that can provide satisfaction in their services. Efforts to meet the needs and expectations of patients can increase the utilization of health services in hospitals. For this reason, hospitals need to carry out marketing activities in order to study and understand patient behavior, where one form is the implementation of the marketing mix. This article aims to determine the effect of the marketing mix on the patient's decision to choose hospital as health care. This study uses a literature review method through the Google Schoolar database source using the keywords